Context-dependent effects of drought and invasive species on population dynamics - Querns, Aleah (My University, 2025)
Invasive species are a major driver of global ecological change and are expected to intensify under future climate scenarios. Yet, the impacts of invaders and their population growth are not uniform and are often shaped by the environmental and management contexts in which they occur. Understanding how these dynamics vary across contexts is essential for predicting invasion trajectories and designing effective management strategies, particularly in vulnerable ecosystems such as grasslands. In this dissertation, I examine how environmental and biotic context shapes both the impacts and performance of plant species, focusing primarily on invasive and encroaching species in grassland ecosystems. In the first component of my work, I examine how herbivory affects population dynamics in the native African subshrub Hibiscus meyeri. Using demographic models, I show that large mammalian herbivores can impede demographic compensation across environmental gradients, primarily due to their influence on the degree of spatial variability in vital rates. In the second component, I use the invasive grass Bromus inermis (smooth brome) to test how its effects on native grass demography varies across rainfall levels. I show that the impacts of brome can be context dependent and differ both across the life stage of native grasses and across rainfall levels. In the final component, I focus on woody encroachment by Juniperus virginiana (eastern red cedar), a native conifer rapidly encroaching in the Great Plains. Using a demographic model, I demonstrate that the invasion speed of red cedar is shaped by interactions among fire, grazing, and climate. Both frequent fires and cattle presence slow invasion, although these effects vary considerably with climate. Together, these results reveal that both invasion processes and species responses more broadly are highly context dependent. The effects of invaders on native species and their own performance are strongly shaped by environmental and management conditions, and similar processes govern native species responses to biotic and abiotic stressors. These findings underscore the need to incorporate environmental variability, management history, and species demography into predictions of invasion dynamics and the development of adaptive, context-specific management strategies.
Keywords: Ecology; Invasion; Plants; Populations; Encroachment